Enhancing Security and Reliability of Information Systems through Blockchain Technology: A Case Study on Impacts and Potential - Adi Nugroho Susanto Putro; Sabil Mokodenseho; Nur Alim Hunawa; Muhatir Mokoginta; Evelin Ragil Marjoni Marjoni (West Science Information System and Technology, 2023)
In the digital age, ensuring the security and reliability of information systems is a paramount concern for organizations. This research investigates the potential of blockchain technology to enhance information system security and reliability within the dynamic landscape of Indonesian start-up companies. By employing a mixed-methods approach, combining qualitative interviews and quantitative surveys, this study explores the current state of information system security practices, assesses the challenges faced by start-ups, and evaluates perceptions regarding the adoption of blockchain technology. The qualitative findings highlight the existing security measures, challenges, and potential benefits associated with blockchain. The quantitative results provide insights into security practices and willingness to adopt blockchain. Through the integration of these findings, the study offers practical recommendations for enhancing information system security and reliability in the context of start-ups, while considering the challenges of blockchain adoption. This research contributes to the understanding of the symbiotic relationship between technology adoption and information security, offering guidance for start-ups, policymakers, and researchers.